Comparison of multifidus muscle intramuscular fat by ultrasound echo intensity and fat-water based MR images in individuals with chronic low back pain. (February 2023) - Crook, Jenna; Masi, Sara; Naghdi, Neda; Roussac, Alexa; Rye, Meaghan; Rosenstein, Brent; Rivaz, Hassan; Boily, Mathieu; Weber, Michael H.; Fortin, Maryse
Abstract: Purpose: The aim of this observational cross-sectional study was to examine correlations of intramuscular fat content in lumbar multifidus (LM) by comparing muscle echo intensity (EI) and percent fat signal fraction (%FSF) generated from ultrasound (US) and magnetic resonance (MR) images, respectively. Methods: MRI and US images from 25 participants (16 females, 9 males) selected from a cohort of patients with chronic low back pain (CLBP) were used. Images were acquired bilaterally, at the L4 and L5 levels (e.g., 4 sites). EI measurements were acquired by manually tracing the cross-sectional border of LM. Mean EI of three US images per site were analyzed (e.g., raw EI). A correction factor for subcutaneous fat thickness (SFT) was also calculated and applied (e.g., corrected EI). Corresponding fat and water MR images were used to acquire %FSF measurements. Intra-rater reliability was assessed by intraclass coefficients (ICC). Pearson correlations and simple linear regression were used to assess the relationship between %FSF, raw EI and corrected EI measurements. Results: The intra-rater ICCs for all measurements were moderate to excellent. Correlations between %FSF vs. raw EI and corrected EI were moderate to strong (0.40 < r < 0.52) and (0.40 < r < 0.51), respectively. Moderate correlations between SFT and EI were also identified. Conclusion: US is a low-cost, non-invasive, accessible, and reliable method to examine muscle composition, and presents a promising solution for assessing and monitoring the effect of different treatment options for CLBP in clinical settings. Highlights: Moderate to strong correlations were found between LM EI and %FSF. Moderate correlations we found between LM EI and SFT. US may be a promising tool to examine LM quality in clinical settings.